Cryopreserved Rat Thyroid Autotransplantation in the Treatment of Postoperative Hypothyroidism - Vasconcellos, Marcel; Carra, Amabile Maran; Franco, Olavo Borges; Baetas-da-Cruz, Wagner; Ferreira, Manoel Luiz; Silva, Paulo Cesar; Lopes de Souza, Sergio Augusto; Miranda-Alves, Leandro; de Carvalho, Denise Pires; Schanaider, Alberto (Frontiers in Endocrinology, 2021)
To verify the viability and functionality of cryopreserved thyroid autotransplantation in rats who underwent total thyroidectomy in the treatment of postoperative hypothyroidism. Thirty-two Wistar rats were randomly assigned into groups (G) with eight animals each: control (CG); simulation (SG); hypothyroidism (HTG) and transplanted (TG). At the beginning and in the 13th week of the experiment, serum levels of total T3, free T4, TSH and calcium were determined. In both the first and 14th weeks, scintigraphic examinations, 99m-Tc pertechnetate radioisotope biodistribution and histopathology were performed. In the 14th week, the expression of proliferating cell nuclear antigen (PCNA) and cellular apoptosis (caspase-3) were also evaluated. In the 13th week, the transplanted animals had normal serum levels of total T3 and free T4. TSH levels showed a tendency towards normality. In the 14th week, scintigraphic exams displayed graft isotopic uptake in all animals in the TG group. Histological examinations 13 weeks after transplantation showed the viability and functionality of thyroid follicles. PCNA revealed significant immunoreactivity of the graft (p < 0.001) when the TG was compared to the CG. There was no difference between CG and TG considering the expression of activated caspase-3. The experimental study confirmed the viability and functionality of thyroid autotransplantation implanted in skeletal muscle with evidence of cell proliferation without cellular apoptosis. This surgical strategy was effective in the treatment of postoperative hypothyroidism.